ANALYSIS OF FACTORS INFLUENCING TOURIST ATTRACTIONS TO HA NAM PROVINCE - Thi Thuy, Duong; Duy Hai, Tong; Duc Thanh, Tran; Quang Tuan, Pham (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
Vietnam’s tourism industry is growing rapidly, creating opportunities for localities to strengthen and position their destination brands. Ha Nam, located at the southern gateway of the Red River Delta with rich yet underutilized tourism resources, faces the strategic challenge of enhancing its destination attractiveness. This study identifies and evaluates the key factors influencing Ha Nam’s tourism appeal through a model comprising five dimensions: (1) natural and cultural resources, (2) infrastructure and technical facilities, (3) quality of human resources in tourism, (4) destination image and security, and (5) digital transformation in tourism. Data were collected from 620 domestic and international tourists visiting major attractions such as Tam Chuc pagoda, Ba Danh pagoda, Ngu Dong Thi Son, Dia Tang pagoda, Cay Thi pagoda, Phat Quang pagoda, Lanh Giang temple and Quyet Thanh pottery village, using a stratified random sampling method. Analysis with SPSS 26.0 employed cronbach’s alpha, exploratory factor analysis, and multiple linear regression. All factor groups achieved cronbach’s alpha above 0.9, KMO above 0.8, and bartlett’s test sig. = 0.000, confirming high reliability and suitability. The model explained 96.2% of the variance (adjusted R² = 0.962) in destination attractiveness, with tourism resources (β = 0.304) and destination image and security (β = 0.295) identified as the most influential. The findings refine the analytical framework for assessing destination attractiveness and provide a scientific foundation for branding and product strategies.